PALEM DI TAMAN NASIONAL BUKIT BAKA-BUKIT RAYA, KALIMANTAN BARAT - Rustiami, Himmah (JURNAL BIOLOGI INDONESIA, 2013)
Field work of palm diversity in Bukit Baka-Bukit Raya National Park had been conducted and revealed 17 species ofpalms, namely Caryota, Iguanura, Licuala, Pinanga, as well as 4 Calamus spp., 5 Daemonorops spp., and 3 Korthalsiaspp. Seven species out of those seventeen species were recorded as endemic in Kalimantan, namely Caryota no,Iguanura macrostachya, Licuala borneensis, Pinanga tomentella, Calamus pogonacanthus, Daemonorops microstachys danDaemonorops sp. 1. Identification key, species description, synonym and other information related to the speciesreported in this paper.Keywords: Palm diversity, Bukit Baka-Bukit Raya National Park, endemic, Kalimantan